Neuroimmunoregulatory potential of seleno-polymannuronate derived from alginate in lipopolysaccharide-stimulated BV2 microglia. (February 2019) - Bi, Decheng; Lai, Qiuxian; Li, Xiaofan; Cai, Nan; Li, Tong; Fang, Weishan; Han, Qingguo; Yu, Boming; Li, Lin; Liu, Qiong; Xu, Hong; Hu, Zhangli; et al.
Abstract: Alginate is an unbranched polymer composed of polymannuronate (PM) and polyguluronate and widely used as a colloid in food industries. Seleno-polymannuronate (Se-PM), a kind of seleno-polysaccharide, was synthesized through selenylation replacement reaction of PM. And its neuroimmunoregulatory activity in LPS-induced BV2 cells and in vivo septic shock model was conducted. Se-PM could significantly attenuate the NO and PGE2 secretion, as well as the iNOS and COX-2 expression, and the release of TNF-α and IL-1β, 6 and 12 in LPS-activated microglia. Meanwhile, the changes in cellular morphology and migration were recovered by pretreating the LPS-activated microglia with Se-PM. Moreover, the overactivation of the NF-κB and MAPK signaling pathways stimulated by LPS in BV2 microglia was prominently alleviated by Se-PM. In the septic shock mouse model, Se-PM could remarkably decrease the TNF-α and IL-6 production in the serum and brain. These results indicate that alginate-derived Se-PM is a good candidate to be used in alternative/supplementary medication or functional foods for treating/managing neurodegenerative disorder. Graphical abstract: Image 1 Highlights: Se-PM inhibits LPS-induced proinflammatory mediator production in BV2 microglia. Se-PM recovers LPS-triggered changes in cellular morphology and migration. Se-PM suppresses LPS-induced over-activation of NF-κB and MAPK signaling pathways. Se-PM attenuates excessive activation of the immune system in vivo.